Prevalência de excesso de peso em mulheres na pós-menopausa e fatores associados - Dias, Lizziane Andrade (2014)
Introduction: The obesity disease has a multifactorial origin, which comes from an overweight condition and is characterized by body fat excess. Many countries has shown a continuously rise on case numbers, constituting a serious problem for public health. Researches revealed that obesity prevails in female population, and the metabolic changes observed on aging favour the gain of body weight in older women. However, factors determining the prevalence of obesity in women isn't completely clear, and the literature evaluating the obesity predominance on menopause are scarce. Objectives: We aim to describe the overweight and obesity prevalence in a postmenopausal women sample enrolled on the Saúde da Família Program (Family Health Program) at São Gonçalo dos Campos city - Bahia. Material e Methods: The cross-sectional study has an exploratory character and a quantitative aspect. We studied 184 women from 50 to 60 years old enrolled on the Saúde da Família Program at São Gonçalo dos Campos city, Bahia. All women had presented amenorrhea for at least 12 months, and consented to be part of research by signing the Informed Consent. In domestic visits we evaluated anthropometry, measuring body weight, height and waist circumference. Trough structured questionnaires we collected sociodemography, reproduction and life style data. The Body Mass Index (BMI) was used to evaluate weight excess; the cut-off point was BMI ≥ 25kg/m². The data analysis was constituted for descriptive analysis, bivariate analysis by calculating the Prevalence Ratio (PR), followed by multivariate analysis trough Poisson regression, robust model using the SPSS software for Windows 17.0. The research project was submitted and approved by Universidade Estadual de Feira de Santana (Feira de Santana Estate University) Ethical Committee (CEP –UEFS). Results: The sample average age of 55,24  2,94 years, and an average BMI of 27,37±5,75. Concerning sociodemographic data, the majority of women had no paid work (81,0%), they had studied until the primary education (64,7%), her familiar income per month was lower or equal the minimum salary (53,8%), they were not using hormone therapy (95,1%), and they had born one or more children (92,9%). The analysis of behaviour variables revealed 11,4% of women smoked regularly, 26,1% used alcoholic beverage, and 70,1% was physically active. The weight excess prevailed on 65,8% of the sample (35,3% of overweight and 30,5% of obesity), and 79,9% revealed raised risk or very raised risk of cardiovascular and metabolic diseases. The multivariate analysis revealed association between overweight and the primary education level (PR= 0,77 CI95%: 0,63; 0,94), the familiar income above the minimum salary (PR= 1,36 CI95%:1,10; 1,70), the non-smoking characteristic (PR= 1,49 CI95%: 0,96; 2,30), and the use of hormone therapy (PR= 0,72 CI95%:0,56;0,94). Conclusions: The high preponderance of weight excess in postmenopausal women confirms the group susceptibility to the presented conditions, therefore we emphasize the necessity of precisely identification of the main factors associated with this weight excess on the construction of future policies aiming its control and the rates decreasing in population.